Extensive clostridial myonecrosis after gluteal intramuscular injection in immunocompromised patient treated with surgical debridement and negative-pressure wound therapy - Laurine Paquier; Jakov Mihanović; Antoine Counil; Robert Karlo; Ivan Bačić; Boris Dželalija (Trauma Case Reports, 2021)
Gas gangrene is infectious disease caused by Clostridium perfringens infection.We are presenting extremely rare case of gluteal clostridial myonecrosis after intramuscular injection of diclofenac in immunocompromised young patient on a long-standing corticosteroid therapy presented with sepsis and initially absent clinical signs of severe anaerobic infection. After delayed diagnosis, she was treated with aggressive surgical removal of necrosed tissue and targeted antibiotic therapy which led to a rapid improvement allowing application of a negative-pressure wound therapy device with favorable outcome.This report shows the importance of timely diagnosis with pitfalls of imaging. It confirms that surgical debridement along with specific antibiotic therapy is the mainstay of treatment, but also promotes negative-pressure wound therapy which has proved convenient for accelerated closure of large incisions with tissue loss without any adverse effects or the need for complex reconstructive procedures.